2016
DOI: 10.1590/s1806-37562015000000133
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the stability of housekeeping gene expression in the left cardiac ventricle of rats submitted to chronic intermittent hypoxia

Abstract: Obstructive sleep apnea (OSA) has been associated with oxidative stress and various cardiovascular consequences, such as increased cardiovascular disease risk. Quantitative real-time PCR is frequently employed to assess changes in gene expression in experimental models. In this study, we analyzed the effects of chronic intermittent hypoxia (an experimental model of OSA) on housekeeping gene expression in the left cardiac ventricle of rats. Analyses via four different approaches-use of the geNorm, BestKeeper, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…When all expression stability values were integrated from the five body parts, the stability rank from the most to least stable was as follows: RAD1a > RPS18 > RPS5 > ARF1 >> GAPDH ( Table 1 and Fig 2A ). Considering a stability value < 0.15 as the criterion for suitable reference gene selection in NormFinder [ 57 , 58 ], all genes were acceptable across different conditions, but GAPDH (stability value = 0.166) was not suggested as a qRT-PCR reference gene for thorax of honey bees exposed to pesticides ( Table 1 and Fig 2A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When all expression stability values were integrated from the five body parts, the stability rank from the most to least stable was as follows: RAD1a > RPS18 > RPS5 > ARF1 >> GAPDH ( Table 1 and Fig 2A ). Considering a stability value < 0.15 as the criterion for suitable reference gene selection in NormFinder [ 57 , 58 ], all genes were acceptable across different conditions, but GAPDH (stability value = 0.166) was not suggested as a qRT-PCR reference gene for thorax of honey bees exposed to pesticides ( Table 1 and Fig 2A ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to RefFinder, three software also analyzed that RAD1a and RPS18 were ranked as the most stable ( Fig 2 ). Based on the criteria: mean stability < 0.15 in NormFinder [ 57 , 58 ], SD value < 1.0 in BestKeeper [ 59 ], and M < 0.5 in geNorm [ 60 , 61 ], the calculated values of both genes were below the cut-off values ( Fig 2 and Tables 1 and S2 – S4 ). C q distribution analysis also revealed CV values < 1, which indicates low variance ( Fig 1 ) [ 56 ], suggesting that the combination of RAD1a and RPS18 can be selected as reference genes for target gene normalization in different body parts from honey bees exposed to various pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the cutoff values in each algorithm, most of the seven candidate genes could be deemed acceptable for use as reference genes when analysing gene expression in different conditions in honey bees. Although most previous studies did not set a cutoff value for gene stability in NormFinder analysis 6 8 , 14 16 , 21 , 22 , several recent studies have suggested values < 0.15 as a suitable cutoff 20 , 26 , 27 . Based on this criterion, all seven genes were suitable reference genes according to NormFinder.…”
Section: Discussionmentioning
confidence: 99%
“…The set of customized assays employed to amplify the genes, namely primers/probes and cycle threshold (Ct) values, are described in Table 1. Expression values were normalized using three different endogenous controls ( beta ‐ actin , GAPDH , and B2 M ), as previously validated by our group for use with the IH protocol (Julian et al, 2016).…”
Section: Methodsmentioning
confidence: 99%